Tinjauan Fatwa DSN MUI No. 85/DSN-MUI/Xii/2012 tentang Perjanjian pada Akad Muzaraah terhadap bagi Hasil Panen Padi - Solihat; Nandang Ihwanudin; Iwan Permana (UNISBA Press, 2022)
Abstract. Muzara'ah contract is a profit sharing system in agriculture where one party owns the land and the other party acts as a cultivator, with a profit sharing system as agreed by both parties. In Cioyod Village the majority are farmers, one of the agricultural products in Cioyod Village is rice. The farmers in Cioyod Village in making cultivation agreements use the muzara'ah system, but its implementation it is suspected that it is not in accordance with the Fatwa of DSN MUI No. 85/DSN-MUI/XII/2012. Researchers in this study formulate the formulation of the problem as follows: How is the practice of sharing the results of the muzara'ah contract in Cioyod Village; How is the review of the DSN MUI fatwa No. 85/DSN-MUI/XII/2012 on the profit sharing agreement of the muzara'ah contract in Cioyod village; The purpose of this research is to answer the problems that occur in Cioyod Village. This research is a field research, using qualitative descriptive analysis techniques. The results of his research that in Cioyod Village the muzara'ah profit sharing system is interpreted as a cooperation agreement; the practice of muzara'ah in Cioyod Village is not in accordance with the DSN MUI Fatwa No. 85/DSN-MUI/XII/2012. Abstrak. Akad Muzara’ah adalah sistem bagi hasil dalam pertanian dimana satu pihak mempunyai lahan dan pihak yang satu berperan sebagai penggarap, dengan sistem bagi hasil sesuai dengan yang telah disepakati oleh kedua belah pihak. Di Kampung Cioyod mayoritas adalah petani, salah satu hasil tani di Kampung Cioyod adalah padi. Para petani di Kampung Cioyod dalam melakukan perjanjian penggarapan menggunakan sistem muzara’ah, akan tetapi pada pelaksanaanya diduga tidak sesuai dengan Fatwa DSN MUI No.85/DSN-MUI/XII/2012. Peneliti dalam penelitian ini merumuskan rumusan masalah sebagai berikut: Bagaimana praktik perjanjian bagi hasil akad muzara’ah di Kampung Cioyod; Bagaimana tinjauan fatwa DSN MUI No.85/DSN-MUI/XII/2012 terhadap perjanjian bagi hasil akad muzara’ah di kampung Cioyod; adapun tujuan dari penelitian ini yaitu menjawab permasalahan yang terjadi di Kampung Cioyod. Penelitian ini merupakan penelitian yang bersifat lapangan, menggunakan teknik analisis deskripstif kualitatif. Hasil penelitiannya bahwa di Kampung Cioyod sistem bagi hasil muzara’ah di artikan sebagai akad kerjasama; praktik muzara’ah di Kampung Cioyod tidak sesuai dengan Fatwa DSN MUI No.85/DSN-MUI/XII/2012.